The injustice - Patterson, James, 1947-; Raymond, Emily, 1972- (Jimmy Patterson Books, 2018)
Expelled over the photo that was posted to his Twitter account, Will Foster, seventeen, is determined to find out who took the picture and why he and three other students were targeted.